National and state-level colorectal cancer mortality trends in Mexico, 1998-2018 - Priscilla Espinosa-Tamez; Erick Suazo-Zepeda; Hugo Sánchez-Blas; Mónica Meneses-Medina; Fidel David Huitzil-Meléndez; Katherine Van Loon; Michael Potter; Martín Lajous (Instituto Nacional de Salud Pública, 2021)
Objective. To describe the burden of colorectal cancer (CRC) in Mexico and understand mortality patterns based on sex, geography, and insurance status. Materials and methods. Mortality data (1998-2018) from the Instituto Nacional de Estadística y Geografía was obtained. We included colon (C18.0, C18.2-18.9) and rectal cancer ICD-10 codes (C19, C20), and estimated age-standardized national, state-level and health insurance mortality rates. We estimated the average annual percent change using joinpoint regression. Results. Between 1998 and 2018, the observed women and men mortality rate increased annually by 1.3 and 2.7%, respectively. Higher CRC mortality was observed in northern and more urbanized states and in groups with greater access to health insurance, which currently facilitates but does not routinely cover screening. Conclusion. CRC mortality in Mexico is increasing rapidly, with marked differences based on sex, geography, and insurance status. Our findings underscore potential benefits of increased investment in comprehensive screening, diagnosis, and treatment strategies for the general population.